Modulation of designer biomimetic matrices for optimized differentiated intestinal epithelial cultures. (March 2022) - Xi, Wang; Saleh, Jad; Yamada, Ayako; Tomba, Caterina; Mercier, Barbara; Janel, Sébastien; Dang, Tien; Soleilhac, Matis; Djemat, Aurélie; Wu, Huiqiong; Romagnolo, Béatrice; Lafont, Frank; et al.
Abstract: The field of intestinal biology is thirstily searching for different culture methods that complement the limitations of organoids, particularly the lack of a differentiated intestinal compartment. While being recognized as an important milestone for basic and translational biological studies, many primary cultures of intestinal epithelium (IE) rely on empirical trials using hydrogels of various stiffness, whose mechanical impact on epithelial organization remains vague until now. Here, we report the development of hydrogel scaffolds with a range of elasticities and their influence on IE expansion, organization, and differentiation. On stiff substrates (>5 kPa), mouse IE cells adopt a flat cell shape and detach in the short-term. In contrast, on soft substrates (80–500 Pa), they sustain for a long-term, pack into high density, develop columnar shape with improved apical-basal polarity and differentiation marker expression, a phenotype reminiscent of features in vivo mouse IE. We then developed a soft gel molding process to produce 3D Matrigel scaffolds of close-to-nature stiffness, which support and maintain a culture of mouse IE into crypt-villus architecture. Thus, the present work is up-to-date informative for the design of biomaterials for ex vivo intestinal models, offering self-renewal in vitro culture that emulates the mouse IE. Highlights: Substrate rigidity guides the organization of intestinal epithelium (IE) and its differentiation. Simple method for long-term in vitro cultures of IE on planar hydrogel substrates. IE monolayers recapitulate features of in vivo intestinal epithelium. 3D scaffolds with mimetic crypt-villus structure are produced using soft hydrogels. Ex vivo 3D intestinal model replicates key features of mouse small intestinal epitheliumManuscript # jbmt56984.